Effect of manganese supplementation on the membrane integrity and the mitochondrial potential of the sperm of grazing Nelore bulls - Reis, L. S. L. S. [UNESP]; Ramos, Alcides Amorim [UNESP]; Camargos, A. S. [UNESP]; Oba, Eunice [UNESP] (Elsevier B.V., 2014)
The effect of dietary manganese (Mn2+) supplementation on the reproductive performance of Nelore bulls was evaluated by assessment of sperm membrane integrity. Sixty Nelore bulls (Bos taurus indicus) aged 18-20 mo were randomly divided into four groups (n = 15) receiving dietary Mn2+ supplementation at 540, 1300, 3800 and 6300 mg/kg (treatments T-c, T-1300, T-3800 and T-6300, respectively). The diets were changed for the groups every 70 d. Semen samples were obtained 15 and 56 d after the diet change, which corresponded to the period of adjustment to the new diet and the time required for a complete spermatogenesis cycle, respectively. Sperm integrity was assessed by detection of: intact (IMe) or damaged (DMe) membranes, intact (IA) or damaged (DA) acrosomes, and high (HM) or low (LM) mitochondrial membrane potentials. Only bulls from the Tc treatment showed a significant increase in the production of intact sperm [IMe/IA/LM] and decrease in the production of sperm with damaged acrosome [IMe/DA/LM] or completely damaged sperm IDMe/DA/LM] (P < 0.05). The Mn2+ concentrations in the semen were positively correlated with the incidence of sperm with IMe, DA, and LM and negatively correlated with number of sperm with DMe, IA, and LM. Therefore, dietary Mn2+ supplementation for Nelore bulls must be limited to 540 mg of Mn2+/kg given that higher doses are detrimental to the integrity of the plasma and acrosomal sperm membranes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Manganese; Spermatozoa; Integrity of sperm membrane and acrosome; Cattle; Mineral salt